Respuesta :

Answer:

The image of point (2, 4) after transformation is (-2, 13) ⇒ D

Step-by-step explanation:

Let us revise some transformation

Translation right-left OR up-down

  • If the function f(x) translated horizontally to the right by h units, then its image is g(x) = f(x - h)  ⇒ add x-coordinate of every point by h
  • If the function f(x) translated horizontally to the left by h units, then its image is g(x) = f(x + h)  subtract x-coordinate of every point by h
  • If the function f(x) translated vertically up by k units, then its image is g(x) = f(x) + k  add y-coordinate of every point by k
  • If the function f(x) translated vertically down by k units, then its image is g(x) = f(x) - k  ⇒ subtract y-coordinate of every point by k

A vertical stretching and a vertical compression (or shrinking)

  • If m > 1, the graph of y = m • f(x) is the graph of f(x) vertically stretched by factor m.  ⇒ multiply every y-coordinate by m
  • If 0 < m < 1 (a fraction), the graph of y = m • f(x) is the graph of f(x) vertically shrunk (or compressed) by factor m  ⇒ multiply every y-coordinate by m

Let us use these rules to solve the question.

∵ Point (2, 4) lies on y = x²

∵ The image of y = x² is y = 3(x + 4)²+1

→ The rules of transformation is y = m(x + h)² + k

m is the scale factor of a vertical stretched

m = 3

→ By using the 5th rule above

∴ The y-coordinate of point (2, 4) should multiply by 3

∴ The image of the point is (2, 4 × 3) = (2, 12)

∵ h is the horizontal translation to the left

h = 4

→ By using the 2nd rule above

∴ The x-coordinate of point (2, 12) should subtract by 4

∴ The image of the point is (2 - 4, 12) = (-2, 12)

∵ k is the vertical translation up

k = 1

→ By using the 3rd rule above

∴ The y-coordinate of point (-2, 12) should add by 1

∴ The image of the point is (-2, 12 + 1) = (-2, 13)

The image of point (2, 4) after transformation is (-2, 13)